(untitled) (The Peerian Journal, 2022)
Coronavirus disease (COVID – 19) was one of the most severe pandemics that the world has ever experienced. The infection can range from asymptomatic, mild to life threatening respiratory distress. It can affect almost every organ of the body including the organ of vision. This review was carried out to facilitate the diagnostics and initiation of comprehensive therapy of neuro-ophthalmic manifestations that occur as a complication of coronavirus disease. Ophthalmic manifestations may be present in the clinical manifestation of COVID-19 infection or they may develop later in rehabilitation period or following the recovery. Ophthalmologists should be aware of the possible associations of ocular diseases with SARS-CoV-2 in order to look for specific signs, advise appropriate tests, diagnose and initiate early treatment for life and vision threatening complications.